Preliminary Observations on Performance of Grafted Planting Material of Terminalia bellerica (Gaertn) Roxb. and it's Economics of Cultivation - Sisodiya, S. P.; Chavada, Z. J.; Amin, A. J.; Singh, Santosh Kumar (Indian Forester, 2010)
The present communication describes the field performance and magnitude of fruit production of grafted plants of Terminalia belleriea. After five year of age plant started producing fruits. At eight year age tree number II, III, IV, XIX and XX produced more than 10 kg of fruits. Tree number XX produced fruits in both flowering seasons after seven year age. Economics of plantation was estimated and projected for per hectare basis indicating the profitability of plantation to the farmers.